Politeness Strategies in the 2020 Biden - Trump Preseidential Debate: A Pragmatic Analysis - Prasatyo, Bayu Andika; Gustary, Devian Try (JETAL: Journal of English Teaching & Applied Linguistic, 2024)
This research explores the use of politeness strategies in the 2020 U.S. Presidential debate between Joe Biden and Donald Trump. The study aims to analyze how each candidate utilized these strategies to navigate the debate and influence public perception. By applying qualitative analysis, the research examines debate transcripts through the lens of Brown and Levinson's politeness theory, while also considering non-verbal cues using McNeill's coding scheme. The results show that Trump frequently employed direct and often confrontational bald-on-record strategies, whereas Biden leaned towards positive politeness, seeking to build a sense of connection with the audience. These findings provide valuable insights into the role of politeness strategies in political communication, highlighting their impact on the dynamics of public discourse.